Implicações tecnológicas no seio dos trabalhadores da Universidade 11 de Novembro diante das políticas de inovação - Jeremias Guilherme Maria (2015)
Higher education in Angola in recent years was characterized by new public policies in order to give the universities greater openings and better quality in the training of senior technicians. Implemented as part of the reorganization of higher education, public policies of expansion, allowed the emergence of new public and private universities. The Cabinda and Zaire provinces include academic Region III and the University November 11 the only public institution of higher education in this geographical constituency. The thesis entitled "Technological Implications among the workers at the University November 11th on innovation policies", has the objective systematic approaches to the Information Technology and Communication and the dynamics of public policies of higher education in Angola. To achieve the goal it was necessary a bibliographical survey of the thematic main concepts of technology and its implications, innovation theories, technology in education, public policies of higher education in the overall context. The specific objectives were as systematic approaches make assumptions about the dynamics of public policies of higher education in Angola in the independence period and the context of the University November 11 (UON) highlighting the role of the executive Angola in the definition and implementation of expansion policies higher education in the country, and the strategic plan of higher abroad staff training. The survey also reveals the main factors that influenced the process of implementation of technological innovations and their impact within the faculty workers, administrative and researchers UON. The research took place between 2012 and 2015 in the periods before, during and after the implementation of innovations concerned, for data collection resorted to interview employees involving teachers, administrative and researchers. The dialectic was the method selected and assisted by intensive and extensive observation techniques. The first allowed the application of structured interview while the second was necessary to use the questionnaire to collect data after interpretation is concluded that workers had a positive attitude for innovation resulting in the institution and to characterize the degree of implications for innovation is moderate but causing changes that can interfere subjective and subjectively in the work environment of employees by the new reality, experiences and behaviors, while others dismissed built historically for them